Genetic Analysis Reveals a Distinct Lineage of Hog Deer (Axis porcinus) in Kratie Province, Cambodia. (4th April 2022) - Gupta, Sandeep Kumar; Kumar, Ajit; van Berkel, Tim; Emsens, Willem-Jan; Singh, Bhim; Puls, Sam; Rin, Naroeun; Jocque, Merlijn
Abstract: The hog deer ( Axis porcinus ) is an endangered cervid with drastic population declines. There are 2 recognized subspecies of hog deer: A. p. porcinus, ranging from Punjab Province in Pakistan, Nepal, and the Northern part of India to Myanmar, and A. p. annamiticus found in Indo-China, Thailand, Laos, Cambodia, and Vietnam. The current geographic range of A. p. annamiticus is still ambiguous. We analyzed variation in the mitochondrial DNA control region (mtDNA CR) to investigate the intra-species structure, differentiation, and demographic history of hog deer from Cambodia (Kratie Province), which we compared with the populations from India and Thailand. We also generated divergence time estimates using a concatenated dataset of complete Cyt b and partial CR. The CR data showed that Cambodian hog deer are genetically differentiated from the mainland Indian and Thai populations, forming a distinct basal clade. The time of divergence indicates that the Cambodian lineage split from the other 2 hog deer lineages around 0.51 Mya, during the Late Pleistocene. The results also suggest strong phylogeographic structure among hog deer: lineage A extends from Terai Arc (foothills of the Himalayas) to Assam, India ( A. p. porcinus ), lineage B from Manipur, India to Thailand ( A. p. annamiticus ), and lineage C is only known from Kratie Province, Cambodia. Lineage A exhibited a higher level of genetic diversity than lineages B and C, with recent demographic stability. Thus, the hog deer population in Kratie Province appears to be a distinct lineage that should be treated as an evolutionarily significant unit.